Correlation between magnesium and alkaline phosphatase from gingival crevicular fluid periodontal diseases - Nila Kasuma (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background: Magnesium is one of the alkaline phosphatase (ALP) cofactor. The amount of magnesium contained infoods affect ALP activity. Increased ALP activity will indicate the level of inflammation in periodontal disease. Elevated inflammation in periodontal disease will change gingivitis to periodontitis, where there has been damage to the bone ssupporting the teeth, and an increasing number of gingival crevicular fluid (GCF). The content of GCF consists of enzymatic and non-enzymatic. Changes in the composition of GCF occurs when the inflammation gets worse. Purpose: This study was aimed to prove the correlation between magnesium and ALP from GCF on periodontal disease. Method: This research involved 60 Minangkabaunese people with 20 healthy samples, 20 mild gingivitis samples, and 20 mild periodontitis samples. GCF was collected by absorbing method. Then ALP level in GCF was measured by using ELISA technique. Magnesium level in Minangkabaunese food was tested by Food Frequency Questionnaire (FFQ).Univariate analysis was performed to describe each variable. To see a normal distribution, Kolmogorov Smirnof Test was used (p>0.05). Unpaired T-test and Pearson correlation test was used to see correlation between ALP and magnesium level in Minangkabaunese food. Result: There is a significant correlation between the levels of ALP and magnesium level in Minangkabaunese food with periodontal disease (p=0.005). ALP is higest on mild periodontitis (137.74±23.01 ng/dl). Magnesium level normal control group is highest (250.14±32.34 mg) and in mild periodontitis is the lowest (110.83±21.04 mg). Corelation between ALP and magnesium level indicates strong correlation with negative direction (r=- 0.907). Conclusion: There is correlation between the levels of alkaline phosphatase and magnesium level on periodontal disease. Increasing inflamation rate will elevate the ALP level.